Reveal the Civilization of Contemporary Islam in Children in India - Mohammad Rashedul (GoAcademica Research & Publishing, 2020)
Civilization and culture in the arm of the continent of India had undergone the rise and fall since the colonialism era until the independence day. It can be illustrated by the domination of political map which had existed since the arrival of foreign nation, especially England until they got their indepence. The condition of Indian society at that time was full of contradiction, religion coflicts, quarrelling, robbery, various race, certain group interest dominating, and etc. From this condition, it born many great islamic political figures like Syeh Ahmad Sirhindi, Shah Waliyullah and the next generation, Sayyid Ahmad Khan and the next generation, Indian Moslem League. Which finally made India and Pakistan Independence (1947 M) and Bangladesh’s (1971M). Next, these three countries, which are the same in term of historical country have also various dynamic and sophisticated improvement of Islam.